Consistent Interpretation of Electrical and Optical Transients in Halide Perovskite Layers and Solar Cells. Issue 46 (23rd October 2021) - Krückemeier, Lisa; Liu, Zhifa; Krogmeier, Benedikt; Rau, Uwe; Kirchartz, Thomas
Abstract: Transient photoluminescence (TPL) and transient photovoltage (TPV) measurements are important and frequently applied methods to study recombination dynamics and charge‐carrier lifetimes in the field of halide‐perovskite photovoltaics. However, large‐signal TPL and small‐signal TPV decay times often correlate poorly and differ by orders of magnitude. In order to generate a quantitative understanding of the differences and similarities between the two methods, the impact of sample type (film vs device), large‐ versus small‐signal analysis, and differences in detection mode (voltage vs. luminescence) are explained using analytical and numerical models compared with experimental data. The main solution to achieving a consistent framework that describes both methods is the calculation of a voltage or carrier density dependent decay time that can be interpreted in terms of a capacitive region, a region dominated by defect‐assisted recombination and a region that is dominated by higher order recombination (radiative and Auger). It is experimentally shown that in the efficient methylammonium lead‐iodide solar cells, effective monomolecular lifetimes ≈2 µs can be consistently measured with TPL and TPV. Furthermore, the shape of the decay time versus voltage or carrier density follows predictions derived from implicit and explicit solutions to differential equations. Abstract : Decay times of measured transient photoluminescence (TPL) and transient photovoltage (TPV) are both used to study recombination in halide perovskites but the decay times often differ substantially. Here, a consistent approach to interpret the decays is presented that allows the different parts of the optical and electrical transients to be correctly interpreted, and explains how they are related to material properties.